Antifungal susceptibility profile of Trichosporon inkin: About three cases of White Piedra (2023)
ABSTRACT: Trichosporon spp. usually cause systemic or superficial infections. Three cases of White Piedra produced by Trichosporon inkin are described. The in vitro antifungal activity to fluconazole, amphotericin B, ketoconazole and caspofungin against the three clinical isolates were evaluated. Sensitivity to fluconazole and ketoconazole was evidenced. However, the treatment of this mycosis is still a challenge.